2003
DOI: 10.1016/j.jcat.2003.08.009
|View full text |Cite
|
Sign up to set email alerts
|

An operando optical fiber UV–vis spectroscopic study of the catalytic decomposition of NO and N2O over Cu-ZSM-5

Abstract: The role of the bis(µ-oxo)dicopper core, i.e., [Cu 2 (µ-O) 2 ] 2+ , in the decomposition of NO and N 2 O by the Cu-ZSM-5 zeolite has been studied with combined operando UV-vis monitoring of the catalyst and on-line GC analysis. An optical fiber was mounted on the outer surface of the quartz wall of the plug-flow reactor and collected the UV-vis diffuse reflectance spectra under true catalytic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
102
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(105 citation statements)
references
References 65 publications
3
102
0
Order By: Relevance
“…5B, by increasing the loading from Cu-1 to Cu-2 might be related to this necessity of having neighbouring Cu-sites, although an increment of the 460 nm band in the respective UV-vis spectra is not obvious, and extended characterization, e.g. using the procedures of Groothaert et al [23] are needed to support this hypothesis. CuO containing mesoporous silica structures have been reported previously by [36], who claim to have synthesized mesoporous silica spheres containing nano-dispersed copper oxides.…”
Section: N 2 O Decompositionmentioning
confidence: 98%
See 2 more Smart Citations
“…5B, by increasing the loading from Cu-1 to Cu-2 might be related to this necessity of having neighbouring Cu-sites, although an increment of the 460 nm band in the respective UV-vis spectra is not obvious, and extended characterization, e.g. using the procedures of Groothaert et al [23] are needed to support this hypothesis. CuO containing mesoporous silica structures have been reported previously by [36], who claim to have synthesized mesoporous silica spheres containing nano-dispersed copper oxides.…”
Section: N 2 O Decompositionmentioning
confidence: 98%
“…Similar to Fe-based catalysts, most of the research in the use of Cu-based catalysts for N 2 O decomposition has been directed at ZSM-5. In a recent study of Groothaert et al [23] it was claimed that catalytic activity is predominantly induced by active species containing two copper ions. Measurement under transient reaction conditions indicated that [Cu 2 (m-O) 2 ] 2+ is formed by O abstraction of N 2 O.…”
Section: N 2 O Decompositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several assignments have been reported for this band. Some authors ascribed the band to the presence of (Cu-O-Cu) 2? species [21][22][23], while other groups assigned it to a bis(l-oxo) dicopper species [18,19,24,25]. Recently, Woertink et al [26] presented additional information on the origin of copper species using a combination of resonance Raman (rR) spectroscopy and density functional theory (DFT).…”
Section: Introductionmentioning
confidence: 99%
“…Noteworthy ones are CuZSM 5 catalysts, which are used in the decompo sition of NO [1,2] and N 2 O [3] to N 2 and O 2 , in the selective reduction of NO x with hydrocarbons [4][5][6], in ethylene aromatization [7], and in other applica tions. Along with aluminosilicate zeolites, alumino phosphate (AlPO) zeolites have also found wide use, including in ethylene oligomerization [8], n butene isomerization [9], and N 2 O decomposition [10].…”
mentioning
confidence: 99%